BEHAVIORAL INTENTION TO USE MOBILE BANKING IN GENERATION Z - Angelica, Mora Argatha; Satria, Dias (Contemporary Studies in Economic, Finance and Banking, 2024)
The objective of this study is to identify, explore, and increase understanding of the key factors influencing Generation Z's intention to use mobile banking. This study surveyed 100 respondents aged 17-26 in Jakarta, Indonesia, using an online questionnaire. The Partial Least Square Structural Equation Modeling (PLS-SEM) method was employed to identify the key factors influencing Generation Z's behavioral intention to use mobile banking. The research findings reveal a relationship between perceived trust, self-efficacy, and social influence in the context of behavioral intention based on the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. However, the perceived risk was found to have an insignificant negative influence. The results provide valuable insights for banks in Jakarta in developing policies and innovations to improve the quality of the financial system.